Quantitative and qualitative diversity of chili (Capsicum spp.) genotypes - ZULFIKAR DAMARALAM SAHID; Muhamad Syukur; Awang Maharijaya; Waras Nurcholis (Society for Indonesian Biodiversity, 2022)
Abstract. Sahid ZD, Syukur M, Maharijaya A, Nurcholis W. 2022. Quantitative and qualitative diversity of chili (Capsicum spp.) genotypes. Biodiversitas 23: 895-901. The diversity of chili species in tropical climate areas, especially Indonesia, is very diverse. Information on the performance of chili both quantitatively and qualitatively is needed to form the basis for future research. This study aimed to obtain qualitative and quantitative character information on several chili genotypes. The results showed that there were differences in chili genotypes based on qualitative and quantitative characters. The genotype that excelled quantitatively in terms of fruit weight was CK 12. In addition, this genotype had a square fruit shape that was absent in other genotypes. The highest number of fruit in this study was indicated by pure lines F8 145291-14-9-3-12-1-1 and Bara. Cluster analysis based on quantitative characters (HCA Analysis) grouped all genotypes into three major groups where the CK 12 genotype separated into one group of its own. The information in this study is very useful for research and development of chili plants.